2019
DOI: 10.1016/j.cmi.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of qPCR for quantifying Leishmania kDNA in different skin layers of patients with American tegumentary leishmaniasis

Abstract: We conclude that superficial sampling can retrieve a greater quantity of parasites. Future studies of the role of transepidermal elimination as a mechanism of host defence in ATL must be performed as there is a considerable quantity of Leishmania kDNA in the epidermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
2
30
0
2
Order By: Relevance
“…The reference standards used in three studies [48][49][50], in addition to considering the criteria defined in the present review, also classified as positives the individuals with: a compatible histopathological examination; a positive MIR or indirect immunofluorescence; no confirmation of a differential diagnosis; and a complete response to pentavalent antimonial treatment. In this way, Gomes et al [48] demonstrated that real-time PCR (qPCR) assays performed better than histopathology, smears or culture and that swabs had similar sensitivity to that of biopsy samples and Sevilha-Santos et al [49] showed the best diagnostic accuracy of qPCR in swabs of the superior dermis. It is interesting to note that the values of accuracy of the qPCR of these studies were lower than that of conventional PCR obtained in the other studies included in the review.…”
Section: Results Not Included In the Meta-analysesmentioning
confidence: 99%
“…The reference standards used in three studies [48][49][50], in addition to considering the criteria defined in the present review, also classified as positives the individuals with: a compatible histopathological examination; a positive MIR or indirect immunofluorescence; no confirmation of a differential diagnosis; and a complete response to pentavalent antimonial treatment. In this way, Gomes et al [48] demonstrated that real-time PCR (qPCR) assays performed better than histopathology, smears or culture and that swabs had similar sensitivity to that of biopsy samples and Sevilha-Santos et al [49] showed the best diagnostic accuracy of qPCR in swabs of the superior dermis. It is interesting to note that the values of accuracy of the qPCR of these studies were lower than that of conventional PCR obtained in the other studies included in the review.…”
Section: Results Not Included In the Meta-analysesmentioning
confidence: 99%
“…Serum samples were subjected to indirect immunofluorescence (IgG against Leishmania donovani ). Conventional and real‐time PCR assays were performed on whole blood DNA using the primer pair 5’‐GGCCCACTATATTACACCAACCCC‐3’ and 5’‐GGGGTAGGGGCGTTCTGCGAA‐3’ (Thermo Fisher Scientific, Waltham, MA, USA), targeted to the minicircle kDNA of Leishmania spp . All patients with at least one positive test underwent a complementary evaluation with blood cell counts, determination of the albumin/globulin ratio and abdominal ultrasonography examination.…”
Section: Frequency Of Positivity In the Three Screening Strategies Evmentioning
confidence: 99%
“…1,2 Real-time PCR (qPCR) is considered a very efficient technique, and it adds quantitative results to clinical analyses. [3][4][5] We aimed to test the accuracy of the combination of a Novy-MacNeal-Nicolle (NNN) medium culture and TaqManbased qPCR analysis for the diagnosis of TL. Sample size was calculated 6 considering a 70% prevalence of ATL in this population 5,7 with a null hypothesis for sensitivity set at 70%, an alternative hypothesis for sensitivity set at 90%, power set at ≥80% and the P-value set to be <0.05.…”
mentioning
confidence: 99%
“…Quantitative and qualitative TaqMan-based qPCR was performed with primers targeting sequences of the kDNA of Leishmania. The primer pair selected was 5 0 -TGC TAT AAA ATC GTA CCA CCC GACA-3 0 and 5 0 -GAA CGG GGT TTC TGT ATG CCA TTT-3 0 with the following specific hydrolysis probe for Leishmania (Viannia) braziliensis: FAM-TTG CAG AAC GCC CCT ACC CAG AGGC-TAMRA (FAM, 6-carboxyfluorescein, TAMRA, 6-carboxyethionyl triamine) (Applied Biosystems â , Foster City, CA, USA) as described elsewhere 4,5,9 (R 2 = 0.949, efficiency = 99.722, slope = À3.329). The limit of quantification of the present standard curve was 1 parasite.…”
mentioning
confidence: 99%
See 1 more Smart Citation